ENDOCRINE DISFUNCTION IN WOMEN WITH PRE-ECLAMPSIA AND ALIMENTARY OBESITY - A. N. Rymashevskii; S. S. Tumanyan; E. M. Frantsiyants; S. V. Tumanyan (Акушерство, гинекология и репродукция)
The aim was to study the renin-angiotensin-aldosterone system (RAAS), the level of leptin and kidney function in women with pre-eclampsia (PE) and alimentary obesity (AO).Materials and methods. The levels of renin, angiotensin II, aldoste-rone, leptin, insulin, cortisol, β2-microglobulin, glomerular filtration rate were measured.Results. We show that RAAS, along with a systemic inflammatory response, is a key factor in the development of pre-eclampsia and its progression. The increasing level of leptin has a direct damaging effect on the tubular system of the kidneys.Conclusions. Stimulating the RAAS aggravates the inflammatory response and endothelial dysfunction in women with PE and AO. Elevated concen-trations of leptin in these women have a direct damaging impact on the kidney tubules.